Who really knows their patients' penicillin adverse drug reaction status? A cross‐sectional survey. Issue 1 (January 2015) - Fehily, S. R.; Stuart, R. L.; Horne, K.; Korman, T. M.; Dendle, C.
Abstract This cross‐sectional survey of patients with adverse drug reactions (ADR) to penicillin and their treating doctor, nurse and pharmacist was undertaken to identify the extent of healthcare workers (HCW) awareness of their patients' ADR, and antibiotic use in hospital. There were 23 (38%) doctors, 53 (87%) nurses and 40 (66%) pharmacists who were aware of their patient's penicillin ADR, despite more than half of their patients receiving antibiotics. Interventions encouraging 'double checking' may improve antibiovigilance.